The intention to adopt model of infrastructure as a service-based e-learning in higher education institutions in Nigeria - Tom, Abubakar Magira (2022)
The global demand for providing education for all in the context of Nigerian Higher Education Institutions signifies the urgent need for an effective and efficient method of delivering e-learning content. Presently, the developed countries are adopting Cloud-Based e-learning for its cost reduction, security, scalability, and the availability of e-learning content 24/7. However, the lack of adoption of the Infrastructure as-a Service-Based E-learning faces a threat to the availability and sustainability of e-learning in Nigeria. Thus, the limited studies on its adoption further demonstrate this. Therefore, this study aims to investigate the factors that influence the Intention to adopt IaaSBEL from the perspective of the ICT directorates top managers. PLS-SEM was used to analyse the data generated from the questionnaire, while interview data were analysed using a thematic approach. The statistical results demonstrated that Relative Advantage, Cost Savings, Service Provider Support, and Government Support were significantly supported while Compatibility, Trust, Security, Top Management Support, and Competitive Pressure were not supported. The moderating variable (Government Support) statistical results show that Relative Advantage was positively supported while Cost Savings and Trust were negatively supported. The findings of this study further demonstrated the significance of the adopted variables as capable of influencing the perception of ICT directorates’ top managers' Intention to adopt the IaaSBEL model based on the TOE and DOI theories, with the addition of other external variables. However, the study observed some limitations with regards to the ICT infrastructure and policies in attaining education for all in Nigeria despite gender, financial, and location constraints. The study further contributes to the theory and practice of IS as well as recommendations to policy makers and cloud vendors. Also, effective e-learning would be available to staff and students towards reducing the budgetary constraints, hence, impacting the society.